Typefaces, Fonts, and Types: Toward a Classification of Fifteenth-Century Gothic "Types". Issue 5 (17th August 2016) - Rial Costas, Benito
ABSTRACT: For more than a century, librarians and bibliographers have supposedly identified and cataloged gothic types using the Proctor-Haebler system and many incunabula collections have been described using it. It is now widely accepted that the Proctor-Haebler system's nomenclature and techniques are uniform and consistent for cataloging rare books and that it is informative about types. This article explains that although the Proctor-Haebler system may help us to identify a printer or a printing office, it confounds different typographic concepts (typeface, font, and type), uses contradictory methods, is based on weak or arguable assumptions, and does not inform us about "types."